Centre to prosecute alleged war crimes in Ukraine opens in The Hague - Euro News (euronews, 2023)
After months of lobbying from Kyiv, the International Centre for the Prosecution of the Crime of Aggression against Ukraine (ICPA) has opened in The Hague, Netherlands. #EuropeNews
Ukraine
Keywords: 2023-07 July; The Natherlands